Biomateriais porosos nanoestruturados à base de polissacarídeos de Spondias purpurea L. e Calotropis procera para sistemas de liberação local de oncocalixona A - Rodrigues, Francisco Alessandro Marinho (2024)
Nanostructured biomaterials are highly relevant to materials science and nanomedicine for the development of innovative medical applications. These materials provide a versatile platform for tissue engineering, regenerative medicine and drug delivery. The aim of this work was to develop hybrid nanostructured composites based on polysaccharides from low value-added plant sources to be applied to the local loading and release of oncocalyxone A (OncoA). Nanostructured porous composites were produced by freeze-drying using a cross-linked polymer matrix based on cellulose nanofibrils from Calotropis procera (ciumeira) and quaternized starch from Spondias purpurea L. (ciriguela). The cellulose nanofibrils, obtained by acid hydrolysis and ultrasonic treatment, had a diameter of 29.4 nm and a length of 0.65 µm, crystallinity of 63.9% and a ζ potential of -30.8 mV. The cationic starch had a ζ potential of +23.0 mV, a nitrogen percentage of 0.52% and a degree of substitution (GS) of 0.065. At the same time, mesoporous silica nanocarriers were synthesized in a spherical shape with a hydrodynamic radius of 527.9 nm and a pore size of 2.96 nm. Using the adsorption equilibrium method, the hollow mesoporous silica nanospheres (NOSM) showed adsorption of 26.07 ± 1.36% for OncoA. In addition, NOSM loaded with OncoA (NOSM@OncoA) were incorporated into porous composites with different proportions of the crosslinked polymer matrix, which showed a crosslinking percentage of between 8.8 and 24.1% and porosity of between 19.8 and 25.6%. In vivo tests using a zebrafish model showed that nanocarried OncoA did not present acute toxicity at the concentrations tested. The porous composites showed a controlled release profile with an initial burst of 20-25% of OncoA released in the first 12 h. The release profiles of the composites were best fitted to the Higuchi and Korsmeyer-Peppas model, indicating a mechanism of association between diffusion and super-case II transport. Thus, the preliminary results suggest that the architecture of nanostructured composites incorporated with NOSM@OncoA may be susceptible to application as bone implants for local loading and release, as well as providing a biocompatible structure for tissue regeneration.